Women and the Piano A History in 50 Lives - Tomes, Susan ca. 20./21. Jh (Yale University Press, 2024)
Women are an essential part of the history of the piano-but how many women pianists can you name? Throughout most of the piano's history, women pianists lacked access to formal training and were excluded from male-dominated performance spaces. Even the modern piano's keys were designed without consideration of women's typically smaller hands. Yet despite their music being largely confined to the domestic sphere, women continued to play, perform, and compose on their own terms. Celebrated pianist and author Susan Tomes traces fifty such women across the piano's history. Including now-famous names such as Clara Schumann and Fanny Mendelssohn, Tomes also highlights overlooked women: from Hélène de Montgeroult, whose playing saved her life during the French Revolution, to Leopoldine Wittgenstein, influential Viennese salonnière, and Hazel Scott, the first Black performer in the United States to have a nationally syndicated TV show. From Maria Szymanowska to Nina Simone, and including interviews with women performing today, this is a much-needed corrective to our understanding of the piano-and a timely testament to women's musical lives